Open-source controller for low-cost and high-speed atomic force microscopy imaging of skin corneocyte nanotextures. (October 2022) - Liao, Hsien-Shun; Akhtar, Imtisal; Werner, Christian; Slipets, Roman; Pereda, Jorge; Wang, Jen-Hung; Raun, Ellen; Nørgaard, Laura Olga; Dons, Frederikke Elisabet; Hwu, Edwin En Te
Graphical abstract: Highlights: An open-source controller is proposed for a high-speed an atomic force microscope. The AFM has a maximum tip-sample velocity of 5, 093 µm/s (9.3 s/frame) The scanning velocity is 100 times higher than that of the original controller. The HS-AFM has a resolution of 512 × 512 pixels and imaging area of 46.3 × 46.3 µm. The low-cost HS-AFM can measure the nanotexture of human skin corneocytes. Abstract: High-speed atomic force microscopes (HS-AFMs) with high temporal resolution enable dynamic phenomena to be visualized at nanoscale resolution. However, HS-AFMs are more complex and costlier than conventional AFMs, and particulars of an open-source HS-AFM controller have not been published before. These high entry barriers hinder the popularization of HS-AFMs in both academic and industrial applications. In addition, HS-AFMs generally have a small imaging area that limits the fields of implementation. This study presents an open-source controller that enables a low-cost simplified AFM to achieve a maximum tip-sample velocity of 5, 093 µm/s (9.3 s/frame, 512 × 512 pixels), which is nearly 100 times higher than that of the original controller. Moreover, the proposed controller doubles the imaging area to 46.3 × 46.3 µm 2 compared to that of the original system. The low-cost HS-AFM can successfully assess the severity of atopic dermatitis (AD) by measuring the nanotexture of human skin corneocytes in constant height DC mode. The open-source controller-based HS-AFM system costs less than 4, 000, which provides resource-limited research institutes with affordable access to high-throughput nanoscale imaging to further expand the HS-AFM research community.